Modal Sosial Masyarakat Pesisir (Studi Kesejahteraan Sosial Petani Rumput Laut di Kabupaten Jeneponto) - Fatimah Azis; Risfaisal Risfaisal; Irda Rosa (Indonesian Journal Publisher, 2022)
Social capital is a set of values or informal norms that are shared among members of an interrelated community group, which are based on the values of trust, norms, and social networks. The purpose of this study is to analyze more deeply the existence of social capital and how the perspective of the Pao Village Community, Jeneponto Regency related to capital. This study is a phenomenological study of 10 informants using the data collection method according to the interview method and qualitatively analyzed in a descriptive way. The results of the study indicate that the existence of the share capital in Pao, Jeneponto Regency is indicated by the implementation still under development.Unity, mutual assistance, and concern of the villagers for one another show the form of trust, social norms and social networks that are still intertwined in the Pao village community. The forms of social capital in society are trust, social networks, social norms and reciprocal relationships (cooperation). The social capital of the Pao Village Community, Jeneponto Regency regarding social capital has various responses. Social capital according to the social view is a description of social institutions, such as social networks, norms, and social beliefs, which facilitate mutually beneficial coordination and cooperation. How to behave and treat others. In addition, someone who always maintains trust will also be maintained, treated and appreciated by others because he is good at taking care of himself.